A Study of Grouping Heuristicson Vehicle Scheduling ProblemBased on Changeable Expenditure Coefficient Model - Yong Zeng; Da-Cheng Liu; Ju-Xuan Li; Xiang-Yu Hou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A kind of vehicle scheduling problem(VSP) with non-full load and combined pick-up and delivery is studied， a changeable expenditure coefficient model according to the actual load is made，and grouping heuristicsalgorithmunder restrictions of vehicleload capacity、working time and mileage is designed to minimize the number of vehicle、the distance of empty load and the useless freight turnover．By programming and calculating，an example proves the algorithm is feasible and effectual. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1913